(3OjhGf GHf CHj MLdIs - (3GHf CHj MLdI , CMeO Hf jMji Hf CHj HcQ GdJdeSGfj, TgGH GdOjf CHh GdYHGS,J (B776 (3g` s ((3Ydj GdOeGUj s)
(3ChdgG (B:s
(3GdMeO ddg GdcQje GdefGf hHYO(B: (3agPG OjhGf XQja jMJhj Ydi cd eYfi dWja, LeYJg ef NGdU cdGej hOQ fXGej, NOeJ Hg GdMVQI GdSGejI GdYGdjI s
(3BNQgG (B:s
(3hbGd QMeg Gddg YLHJ ef GdMQGRj Mjf CeSi jQi GdeG aj GdJNhe HfGXQjg adh UM GdJfGSN bdJ Yfg CQhM GdgOgO EfJbdJ Edjg hbO Je GdOjhGf GdeHGQc s
(3oQJHJ bhGajg Ydi MQha GdgLGAs
(3hgh OjhGf BNQ ZjQ OjhGf GdUHGHIs
(3ebhdI Yf fSNI HNW eDdagGs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs